Effects of Astaxanthin on Miniature Pig Sperm Cryopreservation. (19th April 2018) - Lee, Eunjoo; Kim, Daeyoung
Abstract : The purpose of this study is to evaluate the effects of astaxanthin added to freezing buffer on semen parameters, total sperm oxidation stress after postthawing of boar sperm, and lipid peroxidation (LPO) which is caused by reactive oxygen species (ROS) in sperm membrane. Varying concentrations of astaxanthin (0, 10, 50, 100, and 500  μ M) were used in the freezing buffer during cryopreservation to protect the DNA of thawed miniature pig sperm. Semen parameter was measured using computer-assisted sperm analysis (CASA) for sperm motility, and then ROS rate and oxidative stress of boar sperm were determined using fluorescence-activated cell sorting (FACS). Sperm motility was higher (p < 0.05 ) in the astaxanthin group than in the control group. Sperm motility and the number of progressive motile sperm were higher (p < 0.05 ) in the astaxanthin 500  μ M group than in the control group. In ROS evaluation, the astaxanthin group had lower intracellular O2 and H2 O2 in viable sperm. Yo-Pro-I/HE and PI/H2DCFDA staining as revealed using flow cytometry was lower in astaxanthin groups than in the other groups. As a result, we found that astaxanthin could protect the sperm plasma membrane from free radicals and LPO during boar sperm postthawing.